2020
DOI: 10.5194/nhess-2019-373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Snow Avalanche Detection and Mapping in single, multitemporal, and multiorbital Radar Images from TerraSAR-X and Sentinel-1

Abstract: Abstract. Snow avalanches can endanger people and infrastructure, especially in densely populated mountainous regions. In Switzerland, the public is informed by an avalanche bulletin issued twice a day during winter which is based on weather information and snow and avalanches reports from a network of observers. During bad weather, however, information about occurred avalanches can be scarce or even be missing completely. To asses the potential of weather independent radar satellites we compared manual and au… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Sentinel-1 For processing, we followed the steps described in Leinss et al (2020) but added local resolution weighting (LRW; Small, 2012) to optimize the spatial resolution and to minimize terrain shadow and layover effects. For LRW, two acquisitions from orbits with opposite view directions (ascending looking east and descending looking west) were combined using a weighted average based on the local, terrain dependent resolution of every pixel.…”
Section: Data Preprocessing-radar Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Sentinel-1 For processing, we followed the steps described in Leinss et al (2020) but added local resolution weighting (LRW; Small, 2012) to optimize the spatial resolution and to minimize terrain shadow and layover effects. For LRW, two acquisitions from orbits with opposite view directions (ascending looking east and descending looking west) were combined using a weighted average based on the local, terrain dependent resolution of every pixel.…”
Section: Data Preprocessing-radar Datamentioning
confidence: 99%
“…Radar sensors can detect the increased roughness of the snow surface caused by avalanches Malnes, 2015, Leinss et al 2020). Radar satellites, like RadarSat, TerraSAR-X, and Sentinel-1, have been successfully applied for avalanche mapping in various regions (Eckerstorfer and Malnes, 2015;Vickers et al, 2016;Eckerstorfer et al, 2017;Wesselink et al, 2017;Abermann et al, 2019;Leinss et al, 2020). Selective verification has shown that radar underestimates the avalanche activity to an unknown extent (Eckerstorfer et al, 2017).…”
mentioning
confidence: 99%
See 3 more Smart Citations